1999
DOI: 10.1161/01.atv.19.2.356
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Cerebral MRI Findings to Ultrasonographic Carotid Atherosclerosis in Older Adults

Abstract: Abstract-Cerebral magnetic resonance imaging (MRI) has demonstrated a high prevalence of infarct-like lesions, white matter hyperintensities, and evidence of cerebral atrophy in older adults. While these findings are generally believed to be related to ischemia and atherosclerosis, their relationship to atherosclerosis in the carotid arteries remains to be explored. Study subjects were part of the multicenter Cardiovascular Health Study, a cross-sectional study of 3502 women and men Ն65 years of age undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
160
3
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(182 citation statements)
references
References 46 publications
(52 reference statements)
14
160
3
5
Order By: Relevance
“…A combined analysis of the Rotterdam and Zoetermeer Studies confirmed the finding of a significant positive association between carotid atherosclerosis and white matter lesions [40]. The Cardiovascular Health Study (CHS) found a two-fold increase in the prevalence of brain infarcts in elderly individuals (n=3,502) with calcified carotid plaques [41]. The CHS found that coronary artery calcification was also associated with white matter lesions, other brain abnormalities, and cognitive impairment [13].…”
Section: Discussionmentioning
confidence: 81%
“…A combined analysis of the Rotterdam and Zoetermeer Studies confirmed the finding of a significant positive association between carotid atherosclerosis and white matter lesions [40]. The Cardiovascular Health Study (CHS) found a two-fold increase in the prevalence of brain infarcts in elderly individuals (n=3,502) with calcified carotid plaques [41]. The CHS found that coronary artery calcification was also associated with white matter lesions, other brain abnormalities, and cognitive impairment [13].…”
Section: Discussionmentioning
confidence: 81%
“…Thus, detection using the multifractal analysis of microstructural changes in the white matter, specifically changes related to the early stages of atherosclerosis, before the appearance of visible changes on T2-MRI, is clinically significant. IMT is a strong predictor of cerebrovascular disease, including stroke (Cao et al, 2003;Manolio et al, 1999;O'Leary et al, 1999;Touboul et al, 2000). Therefore, this study's quantitative analysis of deep white matter by multifractal analysis is likely to be useful for predicting the occurrence or prognosis of cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The Cardiovascular Health Study previously demonstrated strong relationships between white matter lesions and carotid IMT and stenosis (37). Kitamura et al reported that increased IMT is a risk factor for stroke in Japanese elderly men (38).…”
Section: Discussionmentioning
confidence: 99%